Some puzzling findings regarding the acquisition of verbs - Joshua Hartshorne; Lauren Skorb; Yujing Huang (Language Development Research, 2023)
On the whole, children acquire frequent words earlier than less frequent words. However, there are other factors at play, such as an early "noun bias" (relative to input frequency, toddlers learn nouns faster than verbs) and a "content-word bias" (content words are acquired disproportionately to function words). This paper follows up reports of a puzzling phenomenon within verb-learning, where "experiencer-object" emotion verbs (A frightened/angered/delighted B) are lower frequency but learned earlier than "experiencer-subject" emotion verbs (A feared/hated/loved B). In addition to the possibility that the aforementioned results are a fluke or due to some confound, prior work has suggested several possible explanations: experiencer-object ("frighten-type") verbs have higher type frequency, encode a causal agent as the sentential subject, and perhaps describe a more salient perspective on the described event. In three experiments, we cast doubt on all three possible explanations. The first experiment replicates and extends the prior findings regarding emotion verbs, ruling out several possible confounds and concerns. The second and third experiments investigate acquisition of chase/flee verbs and give/get verbs, which reveal surprising findings that are not explained by the aforementioned hypotheses. We conclude that these findings indicate a significant hole in our theories of language learning, and that the path forward likely requires a great deal more empirical investigation of the order of acquisition of verbs.